2020
DOI: 10.1007/s10008-020-04771-3
|View full text |Cite
|
Sign up to set email alerts
|

Polysulfonate-doped polyanilines—oxidation of ascorbic acid and dopamine in neutral solution

Abstract: The redox behavior of polyaniline (PANI) doped with polysulfonic acids is studied in slightly acidic and neutral solutions (from pH 4 to pH 7). The dopants used are polystyrene sulfonic acid (PSSA), poly(2-acrylamido-2-methyl-1-propanesulfonic acid) (PAMPSA), and poly-(4,4′-(2,2′-disulfonic acid)-diphenylene-tere-phthalamide) (t-PASA). Thin PANI layers are used in order to identify clearly the redox peak structure. Based on deconvolution of the reductive currents, the pH dependence of the constituent peaks is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
(99 reference statements)
0
5
0
Order By: Relevance
“…According to this route, the oxidation reaction would encompass the insertion of anions, and a consequential swelling of the polymer matrix, whereas the reduction would be accomplished through the expulsion of anionic species and the subsequent shrinking of the polymer volume . Conversely, the use of big-size dopants, such as CS – ions, would determine redox mechanisms based on cation exchange, , where the opposite conformational modification is achieved by the expulsion and insertion of cations during oxidation and reduction processes, respectively (eq ). The collected CV measurements disclosed that the doping process achieved by the incorporation of the large CS – anions produces PDANI phases with rather modest electrochemical activity.…”
Section: Resultsmentioning
confidence: 99%
“…According to this route, the oxidation reaction would encompass the insertion of anions, and a consequential swelling of the polymer matrix, whereas the reduction would be accomplished through the expulsion of anionic species and the subsequent shrinking of the polymer volume . Conversely, the use of big-size dopants, such as CS – ions, would determine redox mechanisms based on cation exchange, , where the opposite conformational modification is achieved by the expulsion and insertion of cations during oxidation and reduction processes, respectively (eq ). The collected CV measurements disclosed that the doping process achieved by the incorporation of the large CS – anions produces PDANI phases with rather modest electrochemical activity.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that polyaniline loses its conductivity when PH is greater than three due to the reduced amount of protonated amines. [ 50 ] Tetraniline, the smallest repeating unit in long‐chain polyaniline, can form precisely ordered crystal domains while retaining the most significant advantages of polyaniline. The resulting crystalline tetra‐aniline nanosheets exhibit a unique crystal domain with highly arranged oligopylaniline molecules, which gives them excellent electronic conductivity (8.37 S cm −1 ) and suitable specific capacitance (601 F g −1 ) through chloride ion‐dominated redox interactions in NaCl neutral electrolytes.…”
Section: Implantable Energy Storage Devicesmentioning
confidence: 99%
“…However, the electrochemical detection of AA can be affected by interference species (such as lactic acid, glucose, dopamine, and uric acid) and contaminations, which results in poor reproducibility and electrode fouling when common electrode materials are used. , To overcome these drawbacks, several nanomaterial-based modified electrodes have been developed. ,, They have been modified with graphene, ,, carbon nanotubes, , nanostructured oxides, conductive polymers, ,, noble metal nanoparticles, ,, and composites …”
Section: Introductionmentioning
confidence: 99%
“…8,9 To overcome these drawbacks, several nanomaterial-based modified electrodes have been developed. 1,2,8 They have been modified with graphene, 3,10,11 carbon nanotubes, 12,13 nanostructured oxides, 14−17 conductive polymers, 2,4,18 noble metal nanoparticles, 1,4,19 and composites. 20 Rare-earth nickelates (RNiO 3 , R = rare-earth lanthanide elements) are a promising candidate to improve the performance of AA detection by electrochemical methods.…”
Section: Introductionmentioning
confidence: 99%